Pragmatic Analysis of 2019 Nigerian Presidential Election-Related Newspaper Cartoons - Oluwafemi Bolanle Jolaoso; Oluwadamilola Bukonla Shojonwo (Hasanuddin University, 2023)
This study undertook a pragmatic analysis of the 2019 Nigerian Presidential Election-Related Newspaper Cartoons to establish the central issues, their contextual underpinning, the engendering pragmatic acts and strategies and their implication to media, society and politics. It was designed to address the knowledge gap created by extant studies which evaded the appraisal of this slant of political discourse that would provide a better understanding of the political cartoons. To address this issue, the paper adopted the Pragmatic acts theory and the theory of social semiotics to account for the ensuing issues and their semiotic significance. The descriptive research design was adopted with a purposive sampling technique to allow for a qualitative analysis of the data selected for the study. Twenty-five cartoons were purposively selected for this paper. The selection was premised on the critical issues that tainted the general elections of 2019. These were subjected to pragma-semiotic analysis. Three discourse issues were identified – partisan contest, electoral fraud, and corruption. These were constrained by six contexts, which are the contexts of rivalry, game, defeat, victory, corruption, and war with the pragmatic acts of satirizing, warning, and sensitizing, strategically crystalized through the strategies of negative lexicalization of opposition, satirisation of politicians’ identity, and invocation of actor’s precedence. It, therefore, concludes on the note that it takes more than a literal sense to understand the construction of political cartoons of criticism and thus needs conscious efforts to unravel the issues and pragma-semiotic means of decoding them. The study hence recommends that political cartoon studies should be initiated and their proliferation should be censored due to their sensitive construction of reality and its implication for media, politics and society.